Los derechos y garantías de los maestros frente al interés superior del niño, niña y adolescente. - Barragán Tumailla, Víctor Hugo (2023)
The importance of this research project entitled "The rights and guarantees of teachers against the best interests of children and adolescents" focuses on carrying out a legal analysis of the rights and guarantees of teachers of Basic Education against the principle of superior interest of the boy, girl and adolescent. It is also to establish the legal system of the rights and guarantees of teachers, as well as the legal regulations related to the best interests of children and adolescents in Ecuador. However, it is necessary to highlight how the best interest of the child affects the development of Basic Education teachers, since they have lost authority within educational establishments, thus limiting the power to implement discipline, as well as comply with what the chair requires for an excellent academic training process, in such a way that the teacher can dictate mandatory activities and order that they be fully carried out without having to reach situations of disrespect, causing verbal discussions, or much worse, causing physical aggression between the teacher and the student due to a situation of disobedience, arrogance and disrespect of the academic subjects. For the present investigation a qualitative approach has been selected, because a legal investigation is going to be carried out and therefore this qualitative investigation will allow us to collect, analyze and interpret all that information that is relevant for the development and support of the topic. proposed. However, the research will also have a quantitative approach, because through it we will achieve the collection of numerical data for later analysis. The techniques that will be used are the interview and the survey; and because it is an investigation in the area of law, the analysis of documents will also be used. I finish by 5 analyzing the data obtained compared with the theory and the law to close the investigation with conclusions and recommendations. Keywords: Rights, Guarantees, Principles, Best Interests of the Child and Adolescent, legality, equity.